THE ROLE OF FOLK PROVERBS IN YUSUF KHOS HAJIB'S WORK "KUTADGU BILIK" - Sharipova Sunbula Ahad qizi (Western European Studies, 2025)
The article explains that Turkish didactic literature, in addition to Islamic sources, also has ancient Turkic roots that express the Turkic worldview by analyzing some old Turkic proverbs used in the work "Kutadgu bilik". Also, the methods of incorporating proverbs and parables into the text used to achieve the poetic goal, and the poetic art of the proverb are described.
Keywords: Kutadgu bilik; Yusuf Khos Hajib; proverb